Peran Mentor Dalam Proses Pembelajaran Kewirausahaan Bagi Penyandang Disabilitas [The Role of Mentors in the Entrepreneurship Learning Process for Persons with Disabilities] - Fransisca Desiana Pranatasari; Wendra Hartono; Meidiahna Kusuma (Universitas Pelita Harapan, 2019)
Entrepreneurship is a good instrument for economic improvement. All citizens can actively develop entrepreneurship in a country, whether they are educated or not, rich or poor, and even people with diabilities can seek their livelihood through a carrer choice as an entrepreneur. Most people with disabilities are reduced in their ability to compete, making it difficult to be accepted at bona fide companies. As a result, many of them do not have jobs thereby reducing their livelihood. The decision to become an entrepreneur is a good solution for people with disabilities. For this reason, there is a need for continuous and integrated learning entrepreneurship carried out by mentors. The formulation of this research problem is what is the role of mentors in the entrepreneurship learning process for people with disabilities. The aim is to realize the role of mentors in the entrepreneurship learning process for people with disabilities, the development of disabled entrepreneurs will also increase. The method used is qualitative descriptive with snowball sampling used for the termination of research resources. The result is the formulation of the role of mentors in the entrepreneurship learning process for people with disability especially to build the character they need to become entrepreneurs.Bahasa Indonesia Abstrak: Kewirausahaan adalah salah satu instrumen yang baik untuk perbaikan ekonomi. Semua warga negara dapat aktif mengembangkan wirausaha di suatu Negara, baik mereka yang berpendidikan atau tidak, kaya dan miskin, bahkan untuk orang-orang cacat yang layak mendapatkan mata pencaharian melalui pilihan karir mereka sebagai wirausaha. Sebagian besar penyandang cacat diturunkan kemampuannya untuk bersaing, sehingga sulit diterima di perusahaan bonafit. Akibatnya, banyak dari mereka tidak memiliki pekerjaan sehingga kehidupan mereka kurang layak. Keputusan untuk menjadi wirausaha adalah solusi yang tepat untuk para penyandang cacat. Untuk itu, perlunya kewirausahaan pembelajaran yang berkelanjutan dan terintegrasi dilakukan oleh mentor kepada mereka. Rumusan masalah penelitian ini adalah bagaimana peran mentor dalam proses pembelajaran kewirausahaan bagi penyandang disabilitas. Tujuannya adalah untuk mewujudkan peran mentor dalam proses pembelajaran kewirausahaan bagi para penyandang cacat, perkembangan wirausaha penyandang cacat juga akan meningkat. Metode yang digunakan adalah deskriptif kualitatif dengan snowball sampling yang digunakan untuk penghentian sumber daya penelitian. Hasilnya adalah formulasi peran mentor dalam proses pembelajaran kewirausahaan bagi para penyandang cacat terutama untuk membangun karakter yang mereka butuhkan untuk menjadi wirausaha.